Global Market Expansion and Strategies of Mobile Telecommunication Company (MTC) in Middle East and North Africa - Hussain, Ismail Elkhalifa (2007)
This case study gives an overview of the wireless telecommunications industry, in specific the MENA region and the analysis of MTC which lies within that region. A comprehensive analysis of MTC is provided through Political, Economics, Social and Technological (PEST) as well as Strengths, Weaknesses, Opportunities and Threat (SWOT) analysis.